MULTI-SECTOR PARTNERSHIPS FOR SUSTAINABLE BUSINESS DEVELOPMENT: LESSONS LEARNED FROM ROUND TABLE INDONESIA - Mudde, Huub; Indrawan, R. Dikky; Fahmi, Idqan (Jurnal Manajemen dan Agribisnis, 2012)
Over a period of three years, Bogor Agricultural University/Institut Pertanian Bogor (IPB) and Maastricht School of Management (MsM) have been executing the multi-annual project Round Table Indonesia, www.roundtableindonesia.net. This project aimed at contributing to the improvement of a sustainable business and investment climate in the Indonesian agricultural sector, by strengthening the knowledge capacity, formulating concrete investment opportunities, and facilitating partnerships. As a result, IPB and MsM have developed courses on sustainable business development and facilitated business projects in poultry, mangosteen, palm oil, shrimps, and tourism. All projects are based on in-depth value chain analyses and roundtable meetings with key stakeholders of government, private sector, academia, and civil society. Linking education and applied research with business development will lead to a stronger and more sustainable Indonesian agricultural sector, being of crucial importance for the Indonesian development as a whole.Keywords: Round Table Indonesia, Sustainable Business Development, Value Chain, Agricultural Sector, IPB, MSM